HUBUNGAN LINGKAR LENGAN ATAS (LILA) IBU HAMIL DENGAN BERAT BADAN BAYI LAHIR - Septa Dwi Insani; Nasution, Naimah; Krisna, Putri (Jurnal Doppler, 2024)
Malnutrition that occurs during pregnancy can have a cumulative impact on the nutritional status of the fetus, which is represented by suboptimal birth weight. A mother who is malnourished will cause the fetus to experience impaired growth and function of the placenta which is reflected by the relatively smaller weight and size of the placenta. One of the frequently used measurements of the nutritional status of pregnant women is using the upper arm circumference (LILA). This study aims to analyze the relationship between LILA of pregnant women and the weight of babies born at Sembiring General Hospital. This quantitative research uses research with an analytical survey design and uses a cross sectional approach. The population in this study were 45 mothers who had given birth, and the sample of this study was 45 mothers who had given birth who were taken by total sampling technique. The research instrument was an observation sheet, data were analyzed using the Chi-Square test. The result of the p value is 0.000 <0.05 so it can be concluded that there is a relationship between LILA of pregnant women and the baby's birth weight at Sembiring General Hospital